Digital trichoblastoma treated with electrochemotherapy in a dog - Dos Anjos, Denner Santos [UNESP]; Rossi, Ygor Amaral; Magalhaes, Larissa Fernandes; Calazans, Sabryna Gouveia [UNESP]; Fonseca-Alves, Carlos Eduardo (Bmj Publishing Group, 2018)
Canine trichoblastoma is a benign tumour derived from the trichoblastic epithelium, commonly affecting the head and neck and, less commonly, the limbs and trunk. Herein, the authors report a case of a dog with digital trichoblastoma successfully treated with electrochemotherapy (ECT). The dog received three sessions of ECT with systemic bleomycin. The tumour volume decreased throughout the ECT sessions, with a complete response after 81 days. The patient presented a disease-free survival of 700 days. ECT may be a better approach than surgery for digital trichoblastomas because it avoids amputating the digit and provides a good cosmetic result.
Keywords: electroporation; bleomycin; Dogs; basal cell carcinoma